(untitled) (Research, Society and Development, 2022)
Objetive: To analyze the violation of the rights of children and adolescents in the state of Paraná, from 2009 to 2015.Method: The violation of children´s and adolescents´ rights in the state of Paraná, Brazil, is investigated by an descriptive, retrospective and transversal study with spatial analysis techniques. Data were retrieved from the Information System for Childhood and Adolescence (SIPIA). Data description and spatial distribution of the violation of rights in the state of Paraná were undertaken by GeoDa 0.9.5-i. Spatial auto-correction was calculated by global Moran (uni- and bi-variate) Index and choropleth maps were undertaken. Results: The nuclear family was the predominant violating agent (88.67%), with family and communitarian conviviality as the main violated right, with 41.02% of cases. Univariate analysis revealed positive auto-co-relationship. High-high and low-high clusters of violation of rights against children and against adolescents were concentrated in the south and center-west regions. There was a significant co-relationship between violation rates of children´s and adolescents´ rights and socio-economic variables, such as illiteracy, Gini Index, earning and urbanization degree. Conclusion: The violence of rights against children and adolescents occurs within the society of the state of Paraná in spite of ensuing laws. There are also difficulties and weaknesses within the Information System for Childhood and Adolescence (SIPIA) and under-registration of cases occurred in many towns even when Tutelary Councils are present.